Assessing spacer acquisition rates in E. coli type I-E CRISPR arrays - Peach, Luke J.; Zhang, Haoyun; Weaver, Brian P.; Boedicker, James Q. (Frontiers in Microbiology, 2025)
CRISPR/Cas is an adaptive defense mechanism protecting prokaryotes from viruses and other potentially harmful genetic elements. Through an adaptation process, short “spacer” sequences, captured from these elements and incorporated into a CRISPR array, provide target specificity for the immune response. CRISPR arrays and array expansion are also central to many emerging biotechnologies. The rates at which spacers integrate into native arrays within bacterial populations have not been quantified. Here, we measure naïve spacer acquisition rates in Escherichia coli Type I-E CRISPR, identify factors that affect these rates, and model this process fundamental to CRISPR/Cas defense. Prolonged Cas1–Cas2 expression produced fewer new spacers per cell on average than predicted by the model. Subsequent experiments revealed that this was due to a mean fitness reduction linked to array-expanded populations. In addition, the expression of heterologous non-homologous end-joining DNA-repair genes was found to augment spacer acquisition rates, translating to enhanced phage infection defense. Together, these results demonstrate the impact of intracellular factors that modulate spacer acquisition and identify an intrinsic fitness effect associated with array-expanded populations.